2009
DOI: 10.1098/rsbl.2009.0435
|View full text |Cite
|
Sign up to set email alerts
|

Mhcpolymorphisms fail to explain the heritability of phytohaemagglutinin-induced skin swelling in a wild passerine

Abstract: Genetic estimates of the variability of immune responses are rarely examined in natural populations because of confounding environmental effects. As a result, and because of the difficulty of pinpointing the genetic determinants of immunity, no study has to our knowledge examined the contribution of specific genes to the heritability of an immune response in wild populations. We cross-fostered nestling house sparrows to disrupt the association between genetic and environmental effects and determine the heritab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
(34 reference statements)
4
11
0
Order By: Relevance
“…However, in this study PHA‐response was unrelated to MHC class II heterozygosity or to the presence of certain alleles in the genome of lesser kestrel nestlings. Although our results should be considered with caution due to sample size constraints, they are in agreement with Bonneaud et al (), who found PHA heritability to be independent from MHC variation. The lack of association between PHA‐response and MHC II variability could stem from the time frame considered, as MHC genotypes had been significantly associated with PHA in chicken, but only after 72 hr post‐injection (Taylor et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, in this study PHA‐response was unrelated to MHC class II heterozygosity or to the presence of certain alleles in the genome of lesser kestrel nestlings. Although our results should be considered with caution due to sample size constraints, they are in agreement with Bonneaud et al (), who found PHA heritability to be independent from MHC variation. The lack of association between PHA‐response and MHC II variability could stem from the time frame considered, as MHC genotypes had been significantly associated with PHA in chicken, but only after 72 hr post‐injection (Taylor et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The quantitative genetics analysis also provided evidence of strong additive genetic effects for body mass (adults and fledglings, h 2 ranging from 0.53 to 0.89) and PHA-mediated immune response (fledglings, h 2 ¼ 0.47-0.55). Particularly, the heritability of response to PHA of avian young was surprisingly high compared with other bird populations estimated using either animal model approach or full-sibling analysis (Ardia and Rice, 2006;Pitala et al, 2007; but see Bonneaud et al, 2009). These heritable traits, melanin-based color traits, body mass and immune response, were correlated at the genetic and/or phenotypic levels.…”
Section: Discussionmentioning
confidence: 86%
“…A potential explanation can be that the relative contribution of POMC gene to these complex traits related to physiology and metabolism is relatively minor compared with its contribution to melanin coloration. Alternatively, the influence of other important candidate genes involved in physiological and metabolic functions, for example, the major histocompatibility complex (Mhc) genes, may be biased among those traits (Bonneaud et al, 2009). The melanocortin system is involved in many different physiological and behavioral functions (Ducrest et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Less information is available from wild species' populations, with contrasting outcomes in the few studies available. Thus, whereas some studies have found support for associations of MHC variation and immunocompetence (Bonneaud, Richard, Faivre, Westerdahl, & Sorci, ; Charbonnel et al, ; Cutrera, Zenuto, & Lacey, ; Kurtz et al, ; Lukasch et al, ), others have provided no clear evidence for their existence (Bonneaud, Sinsheimer, Richard, Chastel, & Sorci, ; Cutrera, Zenuto, & Lacey, ; Ekblom, Hasselquist, & Sæther, ; Montano‐Frías, Vera‐Massieu, Álvarez‐Martínez, Flores‐Morán, & Acevedo‐Whitehouse, ; Rodríguez, Broggi, Alcaide, Negro, & Figuerola, ; Sin et al, ). Such contrasting results may indicate the absence of a general biological association between MHC variation and immunocompetence, which may arise only in certain species, populations and/or ecological contexts.…”
Section: Introductionmentioning
confidence: 99%